Repurposing insulin for Alzheimer’s disease treatment: intranasal delivery of a thermoresponsive nanocarrier-based insulin formulation to the brain - Tanisha Tabassum Sayka Khan; Chun Yuen Jerry Wong; Zara Sheikh; Ali Fathi; Simin Maleknia; Farshad Oveissi; Terence Abrams; Will Knox; Julia van der Hoven; Abi Antonito; Michael Murray; Maree Svolos; et al. (Drug Delivery and Translational Research, 2026)
The Intranasal route provides an effective pathway for insulin delivery to the brain compared to oral/subcutaneous routes as it provides direct access to the brain, bypassing the restrictive blood-brain barrier (BBB), while minimizing systemic exposure. The present study investigated the potential of a thermoresponsive polymer, PNPHO, as a nanocarrier for brain-targeted insulin delivery through the intranasal route, with the aim of repurposing insulin for Alzheimer’s disease treatment. Insulin-loaded nanoparticles (NP) were formulated using an advanced crossflow mixing technology with lower (F1) and higher (F2) PNPHO concentrations and characterised in vitro for size, zeta potential, encapsulation efficiencies, stability, drug deposition, and transport and in vivo for biodistribution. Both F1 and F2 NP demonstrated particle sizes ranging from 35.9 to 49.8 nm with low polydispersity index (< 0.3), negative surface charges, high encapsulation efficiencies (> 99%), and conserved structural integrity post 4 weeks of stability study. NP demonstrated significantly greater in vitro nasal deposition compared to insulin alone. Notably, the PNPHO nanocarrier protected insulin from enzymatic degradation, overcoming a key barrier associated with protein/peptide delivery. In vitro drug transport studies showed an initial delay in NP transport across nasal cells due to PNPHO-mucoadhesive properties, followed by increased transport. Significantly enhanced time-dependent NP transport across the BBB cells compared to insulin alone ( p < 0.0001) confirmed NP’s ability to cross the BBB. In vivo, NP demonstrated prolonged nasal retention and higher brain: serum ratio in mice, suggesting sustained drug release and improved brain delivery compared to insulin alone. Collectively, the study highlight the potential of PNPHO as a promising nanocarrier for achieving targeted and efficient intranasal delivery of insulin to the brain. Graphical Abstract

Phthalate exposure and hepatocellular carcinoma: Unraveling mechanisms through network toxicology - Simin Zhan; Chun Li; Kaiyi Zeng; Yanhao Ran; Chenyu Liu; Yunshuo Zhang; Zekai Zeng; Chuntian Wang; Ziqing Yang (Toxicology, 2025)

Antitumor activity of evodiamine analogs by targeting PKCβI in gemcitabine-resistant pancreatic cancer cells - Eun Seo Bae; Junhwa Hong; Yijae Lim; Woong Sub Byun; Simin Chun; Suckchang Hong; Sang Kook Lee (Phytochemistry Letters, 2025)

A nested case-control study of serum zinc and incident diabetes among Chinese adults: Effect modifications and mediation analysis - Jingli Yang; Zhiyuan Cheng; Desheng Zhang; Tongzhang Zheng; Chun Yin; Simin Liu; Lizhen Zhang; Zhongge Wang; Yufeng Wang; Ruirui Chen; Qian Dou; Yana Bai (Science of The Total Environment, 2024)

Plasma Metabolic Analysis Reveals the Dysregulation of Short-Chain Fatty Acid Metabolism in Parkinson’s Disease - Ao Qi; Lulu Liu; Junjie Zhang; Simei Chen; Simin Xu; Yusen Chen; Lijiang Zhang; Chun Cai (Molecular Neurobiology, 2023)

Dibenzoylmethane Protects Against CCl4-Induced Acute Liver Injury by Activating Nrf2 via JNK, AMPK, and Calcium Signaling - Mingnan Cao; Huixia Wang; Limei Guo; Simin Yang; Chun Liu; Tin Oo Khor; Siwang Yu; Ah-Ng Kong (The AAPS Journal, 2017)